Tissue engineering of the temporomandibular joint : Where do we stand now? - HADDAD, Camille; FLEIHAN, Dalia (International Arab Journal of Dentistry (IAJD), 2017)
Tissue engineering is an alternative to traditional strategies to repair and regenerate temporomandibular joints (TMJ). Nowadays, patients suffering from severe dysfunctions of the TMJ may undergo discectomy, a procedure that consists of removing the damaged disc in hopes of reducing the symptoms. However, tissue engineering presents a potential solution for patients suffering from these disorders, due to the lack of safety and effectiveness of TMJ disc implants. Since 1991, several studies have investigated the possibility of regenerating the articular disc. This literature review aims to expose the new challenges and techniques in TMJ disc tissue engineering whether it concerns cell sourcing, scaffold or bioreactors. As these challenges are overcome, the goal of future studies remains to create a functional biological replacement of the TMJ components.